Tantalum pentoxide powder as well as preparation method and application thereof

By adding sulfuric acid and precipitant in fluorotantalic acid solution, controlling acidity and reaction conditions, high-purity tantalum pentoxide powder was prepared, which solved the problem of insufficient purity and stability in the prior art, and achieved high-purity tantalum oxide powder Improves the stability of preparation and process.

CN119255968AActive Publication Date: 2025-01-03NINGXIA ORIENT TANTALUM INDUSTRY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202480001648.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-01-03
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The purity and process stability of the existing tantalum pentoxide powder are insufficient, and the relationship between Fischer particle size and loose density is not paid attention to.

Method used

By adding sulfuric acid to the fluorotantalic acid solution, the acidity exceeds 2mol/L, adding a precipitant and aging, a tantalum hydroxide slurry is obtained, followed by filtration, drying, calcining and high-temperature heat treatment to control the Fischer particle size The ratio to loose density is greater than 1.5, achieving the preparation of high-purity tantalum oxide powder.

Benefits of technology

Improve the purity and process stability of tantalum oxide powder, ensure that the particle size to density ratio and purity requirements of each production are met, and the temperature in the reactor is increased under the conditions of less energy consumption, achieving high purity 2 pentoxide Preparation of tantalum powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255968A_ABST
    Figure CN119255968A_ABST
Patent Text Reader

Abstract

The invention relates to high-purity tantalum pentoxide powder as well as a preparation method and application thereof. The powder is characterized in that: the ratio of the Fisher particle size to the apparent density test value is greater than 1.5, preferably greater than 2.0, more preferably greater than 2.5, preferably greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.5; more preferably, 2.0 to 15.0, and more preferably, 2.0 to 5.0; and more preferably, the tantalum oxide is 99.995% or above of high-purity tantalum oxide. The preparation method comprises the following steps: (1) adding a fluotantalic acid (H2TaF7) solution into a reaction kettle, adding sulfuric acid into the fluotantalic acid solution to enable the acidity of the fluotantalic acid solution to exceed 2mol / L, controlling the temperature of the reaction kettle to exceed 80 DEG C, adding a precipitator until the pH value of the reaction solution is 8-10, then stopping introducing ammonia, and aging to obtain tantalum hydroxide slurry; (2) filtering and washing the tantalum hydroxide slurry obtained in the step (1), and then carrying out solid-liquid separation to obtain a tantalum hydroxide filter cake; (3) drying the filter cake obtained in the step (2) to obtain tantalum hydroxide powder; (4) calcining the tantalum hydroxide powder obtained in the step (3), and crushing and screening the calcined sample to obtain tantalum pentoxide powder; and (5) carrying out heat treatment on the tantalum pentoxide powder obtained in the step (4) at the temperature of 1000-1500 DEG C to obtain the high-purity tantalum pentoxide powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of powder manufacturing, and more particularly to a high-purity tantalum pentoxide powder and a preparation method and application thereof. Background Art

[0002] Tantalum pentoxide, commonly known as tantalum oxide (the two can be used interchangeably in this article), is the raw material for the production of metallic tantalum and also has important applications in other industrial fields.

[0003] Chinese invention CN114057227B discloses a low-carbon high-purity tantalum pentoxide powder and a method for manufacturing the same, which successfully reduces the carbon content in tantalum oxide to below 15ppm. However, although the obtained C content impurities in the patent are low, the overall purity is still unsatisfactory, and the process stability also has room for improvement. Moreover, it does not pay attention to the relationship between the Fischer particle size and the bulk density. Summary of the invention

[0004] According to a first aspect, the present invention provides a tantalum oxide powder suitable for use as a raw material for preparing tantalum powder by a magnesium reduction method. The tantalum oxide powder has a particle size (in μm) and a bulk density (in g / cm 3 The ratio of the particle size is greater than 1.5 (for example, the particle size of the fiber is 6.78 μm, the bulk density is 2.3 g / cm 3 , the ratio of the two is 6.78÷2.3=2.95).

[0005] The ratio of the Fisher particle size to the bulk density of the tantalum oxide powder of the present invention is greater than 1.5, preferably greater than 2.0, more preferably greater than 2.5, more preferably greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.5; more preferably 2.0-15.0, most preferably 3.0-5.0.

[0006] Preferably, the tantalum oxide powder is a high-purity tantalum oxide powder with a purity of 99.995% or more, and more preferably, the tantalum oxide powder is a high-purity tantalum oxide powder with a purity of 99.999% or more. The inventors have found that the higher the purity of tantalum oxide, the more conducive it is to improving the electrical properties of tantalum powder.

[0007] The second aspect of the present invention provides a method for preparing tantalum oxide powder, characterized in that before adding a precipitant to a fluorotantalic acid (H2TaF7) solution, sulfuric acid is added to the fluorotantalic acid solution to make the acidity of the fluorotantalic acid solution exceed 2 mol / L, preferably the acidity of the fluorotantalic acid solution exceeds 2.2 mol / L, and more preferably 2.5-3.5 mol / L.

[0008] Preferably, the method comprises:

[0009] (1) adding a fluorotantalate (H2TaF7) solution into a reaction kettle, adding sulfuric acid to make the acidity of the fluorotantalate solution at least 2 mol / L, adding a precipitant (e.g., passing ammonia gas) until the pH of the reaction solution is 8 to 10 (preferably 8 to 9.5), then stopping the addition of the precipitant, and aging (e.g., aging for 2 to 5 hours, preferably 3 to 4 hours) to obtain a tantalum hydroxide slurry;

[0010] (2) filtering and washing the tantalum hydroxide slurry obtained in step (1), and then performing solid-liquid separation to obtain a tantalum hydroxide filter cake;

[0011] (3) drying the filter cake obtained in step (2) to obtain tantalum hydroxide powder;

[0012] (4) calcining the tantalum hydroxide powder obtained in step (3), crushing and sieving the calcined sample to obtain tantalum pentoxide powder; and

[0013] (5) The tantalum pentoxide powder obtained in step (4) is heat treated at a temperature of 1000° C. to 1500° C. to obtain high-purity tantalum pentoxide powder.

[0014] In step (1), the preferred acidity range is 2 mol / L-5 mol / L. More preferably, when the pH of the reaction solution in step (1) is 8-9, the addition of the precipitant is stopped.

[0015] In step (1), the fluorotantalate solution may be heated, and the temperature of the reactor may be controlled to be above 60°C, preferably above 80°C, and more preferably 85-95°C.

[0016] In step (1), preferably, the oxide content of the fluorotantalate (H2TaF7) solution is 20 to 120 g / L, more preferably 30 to 110 g / L, for example 40 to 100 g / L, calculated in terms of Ta2O5. Advantageously, this wider range brings greater process flexibility. "Calculated in terms of Ta2O5" is clear to those skilled in the art. However, in order to make it easier for those skilled in the art to understand, the inventors explain "calculated in terms of Ta2O5" as follows: This is a commonly used method for expressing the concentration of a fluorotantalate solution (sometimes referred to herein as "tantalate solution"). Tantalum in the fluorotantalate solution mainly exists in the form of a complex. During the determination process, the tantalum content in the fluorotantalate is detected and then converted into the content of Ta2O5 to express the concentration of the tantalate solution, with specific reference to the national standard GB / T15076.1.

[0017] In step (1), the precipitant includes, but is not limited to, one or more of sodium bicarbonate, ammonium carbonate, urea, ammonia water, ammonia gas, and sodium hydroxide. Preferably, ammonia gas is used as the precipitant; in this case, adding the precipitant can also be referred to as introducing ammonia gas. There is no limit on the rate of introducing ammonia gas, but it is preferably introduced slowly. In step (1), stirring is preferably performed in the reactor.

[0018] Preferably, the aging time (also referred to as the resting time) in step (2) is 2 to 5 hours. More preferably, the aging time is 3 to 4 hours. Preferably, the filtration and washing in step (2) is repeated multiple times. For example, the filtration and washing can be performed in the following manner: the tantalum hydroxide slurry obtained in step (1) is added to a filtration and washing tank, and then filtered and washed with hot pure water (e.g., hot pure water at 90 to 100° C.). Preferably, the solid-liquid separation is performed by negative pressure filtration.

[0019] Preferably, in step (3), drying is performed by placing the filter cake in a hot air oven and drying at 80-180° C. (preferably 100-160° C., more preferably 120-140° C.), for example, drying for 8 h to 12 h (preferably 10-11.5 h). The tantalum hydroxide powder obtained in this step is generally white.

[0020] Preferably, the calcination in step (4) is preferably carried out by charging the tantalum pentoxide powder obtained in step (3) into a crucible and placing it in a furnace. The furnace used here is preferably a muffle furnace. Preferably, the calcination temperature is 900°C to 1000°C (preferably 800°C to 900°C), and the calcination time is 8h to 12h (preferably 9-11h).

[0021] The high temperature calcination heat treatment temperature in step (5) is preferably 1200°C to 1500°C (e.g. 1400°C), and the time is preferably 1 to 3 hours. In step (5), the sintering heat treatment atmosphere includes but is not limited to vacuum, inert atmosphere (e.g. helium, argon, neon, etc.) and air atmosphere. It is more preferably carried out under vacuum.

[0022] Preferably, the high temperature vacuum heat treatment temperature in step (5) is 1200° C. to 1400° C., more preferably 1200 to 1300° C.). Preferably, the heat treatment time is 1 h to 5 h, such as 3 h.

[0023] Preferably, the ratio of the Fisher particle size to the bulk density of the tantalum oxide powder obtained in step (5) is greater than 1.5, preferably greater than 2.0, more preferably greater than 2.5, more preferably greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.5; more preferably 2.0-15.0, more preferably 3.0-5.0. More preferably, the tantalum oxide powder is 99.995%, more preferably 99.999% or more pure tantalum oxide.

[0024] The inventors have found through a large number of experiments that the use of a higher acidity as described in step (1) can increase the temperature in the reactor while consuming less external energy due to the heat released by the neutralization reaction. Moreover, the inventors unexpectedly found that the use of such an acidity can stably produce the tantalum oxide powder according to the first aspect of the present invention. The so-called "stable" means that the tantalum powder produced each time can meet the ratio of particle size to bulk density and purity requirements specified in the present invention, and there will be no situation where the process meets the requirements this time but not the next time, or only one of the two is met at a certain time. In terms of process stability, the selection of acidity in step (1) (especially with the help of sulfuric acid) has achieved outstanding and unexpected beneficial effects.

[0025] The overall purity mentioned in this article focuses more on the sum of all impurity contents rather than being limited to the content of one or more common impurities.

[0026] The third aspect of the present invention also relates to the use of the above-mentioned tantalum oxide powder, for example, in the electronics industry, for making lithium tantalate single crystals and manufacturing optical glass (especially high-refractive and low-dispersion special optical glass), and can be used as a catalyst in the chemical industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The following drawings are provided to aid in understanding the present invention. The drawings are not intended to limit the scope of the present invention.

[0028] Figure 1 : An electron microscope photograph of the tantalum oxide powder according to the first aspect of the present invention or the tantalum oxide powder obtained by the method according to the second aspect. The figure shows that the microstructure is improved. DETAILED DESCRIPTION

[0029] In order to better illustrate the present invention, the following examples are provided. These examples are only for better enabling those skilled in the art to more easily understand the present invention, and are not intended to limit the present invention.

[0030] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0031] For the purpose of this specification, all numbers indicating the amount of ingredients, reaction conditions, etc. in the specification and claims should be understood as being modified by the term "about" in all cases, unless otherwise specified. Accordingly, the numerical parameters given in the following specification and the appended claims are approximate values, which may vary according to the desired properties that the present invention attempts to obtain, unless otherwise indicated. At least, and without intending to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be interpreted at least in accordance with the number of reported significant figures and in accordance with conventional rounding techniques.

[0032] The impurity content of tantalum pentoxide powder is analyzed according to the national standard GB / T15076.8, the Fisher particle size is analyzed according to the provisions of the national standard GB / T3249, and the bulk density is analyzed according to the provisions of the national standard GB / T1479.1.

[0033] Embodiment 1:

[0034] 1. Take 100L of tantalate fluoride solution, the oxide content of which is 90g / L calculated as Ta2O5, add it to the reactor, then add sulfuric acid to adjust the acidity of the tantalate fluoride solution to 2.8mol / L, heat the tantalate fluoride solution, and control the temperature of the reactor to 95°C. Slowly pass ammonia water into the tantalate solution until the pH of the reaction solution is 9 to obtain tantalum hydroxide slurry, which is then aged for 3h.

[0035] 2. The tantalum hydroxide slurry is transferred into a filter washing tank, and the reaction precipitate is repeatedly filtered and washed with hot pure water at a temperature of 95°C. Finally, negative pressure filtration is used for solid-liquid separation to obtain a white filter cake.

[0036] 3. Put the white filter cake into a tray, place it in a hot air oven, and dry it at 100°C for 10 hours to obtain tantalum hydroxide white powder.

[0037] 4. Put the white tantalum hydroxide powder into a crucible and place it in a muffle furnace for calcination at a temperature of 900°C for 10 hours. Crush and sieve the sintered sample to obtain tantalum pentoxide powder.

[0038] 5. Put the tantalum pentoxide powder into a crucible, place it in a high-temperature vacuum furnace, and heat it at 1300° C. for 2 hours to perform heat treatment to obtain high-purity tantalum pentoxide powder.

[0039] The impurity content of the tantalum pentoxide powder was analyzed and the purity of tantalum oxide was calculated. The Fisher particle size and bulk density were analyzed and the ratio of the Fisher particle size to the bulk density test value was calculated. The measured results are listed in Table 1.

[0040] Embodiment 2:

[0041] 1. Measure 100L of tantalate fluoride solution, the oxide content of which is 90g / L calculated as Ta2O5, add it to the reactor, then add sulfuric acid to adjust the acidity of the tantalate fluoride solution to 2.2mol / L, heat the tantalate fluoride solution, and control the temperature of the reactor to 85°C. Slowly pass ammonia water into the tantalate solution until the pH of the reaction solution is 9, and obtain tantalum hydroxide slurry, which is aged for 3h.

[0042] 2. The tantalum hydroxide slurry is transferred into a filter washing tank, and the reaction precipitate is repeatedly filtered and washed with hot pure water at a temperature of 95°C. Finally, negative pressure filtration is used for solid-liquid separation to obtain a white filter cake.

[0043] 3. Put the white filter cake into a tray, place it in a hot air oven, and dry it at 100°C for 10 hours to obtain tantalum hydroxide white powder.

[0044] 4. Put the white tantalum hydroxide powder into a crucible and place it in a muffle furnace for calcination at a temperature of 900°C for 10 hours. Crush and sieve the sintered sample to obtain tantalum pentoxide powder.

[0045] 5. The tantalum pentoxide powder is loaded into a crucible, placed in a high-temperature vacuum furnace, and heated at 1350° C. for 2 hours for heat treatment to obtain high-purity tantalum pentoxide powder.

[0046] The impurity content of the tantalum pentoxide powder was analyzed and the purity of tantalum oxide was calculated. The Fisher particle size and bulk density were analyzed and the ratio of the Fisher particle size to the bulk density test value was calculated. The measured results are listed in Table 1.

[0047] Embodiment 3:

[0048] 1. Take 100L of tantalate fluoride solution, the oxide content of which is 60g / L calculated as Ta2O5, add it to the reactor, then add sulfuric acid to adjust the acidity of the tantalate fluoride solution to 2.5mol / L, heat the tantalate fluoride solution, and control the temperature of the reactor to 82°C. Slowly pass ammonia water into the tantalate solution until the pH of the reaction solution is 10, and obtain tantalum hydroxide slurry, which is aged for 3h.

[0049] 2. The tantalum hydroxide slurry is transferred into a filter washing tank, and the reaction precipitate is repeatedly filtered and washed with hot pure water at a temperature of 95°C. Finally, negative pressure filtration is used for solid-liquid separation to obtain a white filter cake.

[0050] 3. Put the white filter cake into a material tray, place it in a hot air oven, and dry it at 100°C for 10 hours to obtain tantalum hydroxide white powder.

[0051] 4. Put the white tantalum hydroxide powder into a crucible and place it in a muffle furnace for calcination at a temperature of 800°C for 10 hours. Crush and sieve the sintered sample to obtain tantalum pentoxide powder.

[0052] 5. Put the tantalum pentoxide powder into a crucible, place it in a high-temperature vacuum furnace, and heat it at 1200° C. for 2 hours to perform heat treatment to obtain high-purity tantalum pentoxide powder.

[0053] The impurity content of the tantalum pentoxide powder was analyzed and the purity of tantalum oxide was calculated. The Fisher particle size and bulk density were analyzed and the ratio of the Fisher particle size to the bulk density test value was calculated. The measured results are listed in Table 1.

[0054] Embodiment 4:

[0055] 1. Take 100L of tantalate fluoride solution, the oxide content of which is 50g / L calculated as Ta2O5, add it to the reactor, then add sulfuric acid to adjust the acidity of the tantalate fluoride solution to 2.5mol / L, heat the tantalate fluoride solution, and control the temperature of the reactor to 85°C. Slowly pass ammonia water into the tantalate solution until the pH of the reaction solution is 10, and obtain tantalum hydroxide slurry, which is aged for 3h.

[0056] 2. The tantalum hydroxide slurry is transferred into a filter washing tank, and the reaction precipitate is repeatedly filtered and washed with hot pure water at a temperature of 95°C. Finally, negative pressure filtration is used for solid-liquid separation to obtain a white filter cake.

[0057] 3. Put the white filter cake into a material tray, place it in a hot air oven, and dry it at 100°C for 10 hours to obtain tantalum hydroxide white powder.

[0058] 4. Put the white tantalum hydroxide powder into a crucible and place it in a muffle furnace for calcination at a temperature of 800°C for 10 hours. Crush and sieve the sintered sample to obtain tantalum pentoxide powder.

[0059] 5. The tantalum pentoxide powder is loaded into a crucible, placed in a high-temperature vacuum furnace, and heated at 1250° C. for 2 hours for heat treatment to obtain high-purity tantalum pentoxide powder.

[0060] The impurity content of the tantalum pentoxide powder was analyzed and the purity of tantalum oxide was calculated. The Fisher particle size and bulk density were analyzed and the ratio of the Fisher particle size to the bulk density test value was calculated. The measured results are listed in Table 1.

[0061] Embodiment 5:

[0062] 1. Take 100L of tantalate fluoride solution, the oxide content of which is 35g / L calculated as Ta2O5, add it to the reactor, then add sulfuric acid to adjust the acidity of the tantalate fluoride solution to 2.5mol / L, heat the tantalate fluoride solution, and control the temperature of the reactor to 85°C. Slowly pass ammonia water into the tantalate solution until the pH of the reaction solution is 10, and obtain tantalum hydroxide slurry, which is aged for 3h.

[0063] 2. The tantalum hydroxide slurry is transferred into a filter washing tank, and the reaction precipitate is repeatedly filtered and washed with hot pure water at a temperature of 95°C. Finally, negative pressure filtration is used for solid-liquid separation to obtain a white filter cake.

[0064] 3. Put the white filter cake into a material tray, place it in a hot air oven, and dry it at 100°C for 10 hours to obtain tantalum hydroxide white powder.

[0065] 4. Put the white tantalum hydroxide powder into a crucible and place it in a muffle furnace for calcination at a temperature of 800°C for 10 hours. Crush and sieve the sintered sample to obtain tantalum pentoxide powder.

[0066] 5. The tantalum pentoxide powder is loaded into a crucible, placed in a high-temperature vacuum furnace, and heated at 1150° C. for 2 hours for heat treatment to obtain high-purity tantalum pentoxide powder.

[0067] The impurity content of the tantalum pentoxide powder was analyzed and the purity of tantalum oxide was calculated. The Fisher particle size and bulk density were analyzed and the ratio of the Fisher particle size to the bulk density test value was calculated. The measured results are listed in Table 1.

[0068] Embodiment 6:

[0069] 1. Measure 100L of fluorotantalate solution, whose oxide content is 25g / L calculated as Ta2O5, and add it to the reactor. Then add sulfuric acid to adjust the acidity of the fluorotantalate solution to 2.5mol / L, heat the fluorotantalate solution, and control the temperature of the reactor to 85°C. Slowly pass ammonia water into the tantalate solution until the pH of the reaction solution is 10 to obtain tantalum hydroxide slurry, which is aged for 3h.

[0070] 2. The tantalum hydroxide slurry is transferred into a filter washing tank, and the reaction precipitate is repeatedly filtered and washed with hot pure water at a temperature of 95°C. Finally, negative pressure filtration is used for solid-liquid separation to obtain a white filter cake.

[0071] 3. Put the white filter cake into a material tray, place it in a hot air oven, and dry it at 100°C for 10 hours to obtain tantalum hydroxide white powder.

[0072] 4. Put the white tantalum hydroxide powder into a crucible and place it in a muffle furnace for calcination at a temperature of 800°C for 10 hours. Crush and sieve the sintered sample to obtain tantalum pentoxide powder.

[0073] 5. The tantalum pentoxide powder is loaded into a crucible, placed in a high-temperature vacuum furnace, and heated at 1150° C. for 2 hours for heat treatment to obtain high-purity tantalum pentoxide powder.

[0074] The impurity content of the tantalum pentoxide powder was analyzed and the purity of tantalum oxide was calculated. The Fisher particle size and bulk density were analyzed and the ratio of the Fisher particle size to the bulk density test value was calculated. The measured results are listed in Table 1.

[0075] Table 1 Analysis results of high purity tantalum pentoxide

[0076]

[0077] As can be seen from Table 1, the ratio of the Fischer-Tropsch particle size to the bulk density of the tantalum pentoxide powder obtained by the method of the present invention is obviously ideal, and in particular, its purity reaches 99.999%.

Claims

1. A tantalum pentoxide powder, characterized in that: The ratio of Fisher particle size to bulk density is greater than 1.5, preferably greater than 2.0, more preferably greater than 2.5, more preferably greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.5; more preferably 2.0-15.0, more preferably 3.0-5.0; more preferably 99.995%, most preferably 99.999% or more purity of tantalum oxide.

2. A method for preparing tantalum pentoxide powder, characterized in that: Sulfuric acid is added to the fluorotantalate solution to make the acidity of the fluorotantalate solution exceed 2 mol / L, preferably the acidity of the fluorotantalate solution exceeds 2.2 mol / L, more preferably 2.5-3.5 mol / L.

3. A method for preparing tantalum pentoxide powder, the method comprising: (1) adding a fluorotantalate (H2TaF7) solution into a reaction kettle, adding sulfuric acid into the fluorotantalate solution to make the acidity of the fluorotantalate solution exceed 2 mol / L, controlling the temperature of the reaction kettle to be above 80°C (preferably above 85°C, more preferably 85-95°C), adding a precipitant until the pH of the reaction solution is 8-10 (preferably 8-9.5), then stopping the flow of ammonia, and performing aging (for example, aging for 2-5 hours, preferably 3-4 hours) to obtain tantalum hydroxide slurry; (2) filtering and washing the tantalum hydroxide slurry obtained in step (1), and then performing solid-liquid separation to obtain a tantalum hydroxide filter cake; (3) drying the filter cake obtained in step (2) to obtain tantalum hydroxide powder; (4) calcining the tantalum hydroxide powder obtained in step (3), crushing and sieving the calcined sample to obtain tantalum pentoxide powder; and (5) The tantalum pentoxide powder obtained in step (4) is heat treated at a temperature of 1000° C. to 1500° C. to obtain high-purity tantalum pentoxide powder. More preferably, in step (1), when the pH of the reaction solution is between 8 and 9, the addition of the precipitant is stopped.

4. The method according to claim 3, wherein in step (1), the precipitant is selected from one or more of sodium bicarbonate, ammonium carbonate, urea, ammonia water, ammonia gas, and sodium hydroxide, preferably, ammonia water is used as the precipitant; and / or preferably, stirring is performed in the reactor, more preferably, the stirring time is 5 to 10 min.

5. The method according to any one of claims 3-4, wherein the aging time in step (2) is 2 to 5 hours, more preferably 3 to 4 hours; and / or wherein preferably, the filtration and washing in step (2) are repeated multiple times; and / or wherein in step (2), solid-liquid separation is performed by negative pressure filtration.

6. The method according to any one of claims 3 to 5, wherein in step (3), drying is carried out by placing the filter cake in a hot air oven and drying it at 80 to 180° C. (preferably 100 to 160° C., more preferably 120 to 140° C.), for example, drying for 8 h to 12 h (preferably 10 to 11.5 h).

7. The method according to any one of claims 3 to 6, wherein the calcination in step (4) is carried out by: charging the tantalum hydroxide powder obtained in step (3) into a crucible and placing it in a furnace, wherein the furnace used is preferably a muffle furnace; preferably, the calcination temperature is 900° C. to 1000° C., and the calcination time is preferably 8 h to 12 h (preferably 9-11 h).

8. The method according to any one of claims 3 to 7, wherein in the step (5), the high temperature heat treatment temperature is preferably 1200°C to 1500°C (preferably 1200°C to 1400°C, for example 1400°C, more preferably 1200-1300°C), and the time is preferably 1 to 5 hours; and / or wherein preferably, the sintering heat treatment atmosphere includes but is not limited to vacuum, inert atmosphere (for example helium, argon, neon, etc.) and atmospheric atmosphere, and is more preferably carried out under vacuum.

9. Tantalum pentoxide powder obtained according to the method of any one of claims 3 to 8, preferably the powder has a ratio of Fisher particle size to bulk density test value greater than 1.5, preferably greater than 2.0, more preferably greater than 2.5, more preferably greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.5; more preferably 2.0-15.0, more preferably 3.0-5.0; more preferably 99.995% or more high purity tantalum oxide.

10. Use of the tantalum pentoxide powder according to claim 1 or 9 in the production of lithium tantalate single crystals and catalysts and in the production of optical glass.

Citation Information

Patent Citations

  • Ultra-high-purity tantalum oxide and method for preparing same

    CN104386751A

  • Cosolvent method used for growth of uniform near-stoichiometric lithium tantalate crystals

    CN110241456A

  • Preparation method of high-purity niobium oxide for high-purity niobium sheet for irradiation monitoring pipe

    CN112010348A

  • Low-carbon high-purity tantalum pentoxide powder and preparation method and application thereof

    CN114057227A

  • Method for preparing tantalum pentoxide with large apparent density by chemical method

    CN116969509A